PENGARUH E-SERVICE QUALITY DAN BRAND IMAGE TERHADAP KEPUASAN KONSUMEN - Eko Budiyanto; Ichwan Bagus Airlangga; Ali Mahsun (Fakultas Ekonomi Universitas Yos Soedarso, 2019)
This study aimed to determine whether or not: 1) e-service quality influences customer satisfaction, 2) e-service quality influences customer loyalty, 3) brand image influences customer satisfaction, 4) brand image influences customer loyalty, customer satisfaction influences customer loyalty, 6) customer satisfaction mediates the influence of e-service quality towards customer loyalty, 7) customer satisfaction mediates the influence of brand image towards customer loyalty. In this research, the sample selection technique used is purposive sampling with 105 respondents. Then, the data analysis technique used is Partial Least Square by using warpPLS 6.0 application. The analysis reveals that: 1) e-service quality had a positive influence towards customer satisfaction, 2) e-service quality had a positive influence towards customer loyalty, 3) brand image had a positive influence towards customer satisfaction, 4) brand image had a positive influence towards customer loyalty, 5) customer satisfaction had a positive influence towards customer loyalty, 6) customer satisfaction mediated the influence of e-service quality towards customer loyalty, 7) customer satisfaction mediated the influence of brand image towards customer loyalty. Keywords : E-Service Quality; Brand Image; Customer Satisfaction; Customer Loyalty.